PENGOLAHAN LIMBAH PERTANIAN DAN PETERNAKAN SEBAGAI PUPUK ORGANIK DI DESA SUMBER BENING - Linna Fitriani; Destien Atmi Arisandy (LP4MK STKIP PGRI Lubuklinggau, 2022)
Program kemitraan masyarakat (PKM) aims to overcome the problem of agricultural waste and livestock waste, the lack of fertilizer which is needed by agricultural groups by utilizing agricultural waste and livestock waste into organic fertilizer that can be used sustainably for agriculture in Sumber Bening. This PKM is expected to increase the knowledge and skills of farmers in the supply of organic fertilizers in agriculture so that there is an increase in the economy. Processing of organic fertilizer from agricultural and livestock waste began with outreach, training, mentoring and evaluation of product results on an ongoing basis. Based on the activities carried out, there was an increase in knowledge of 49%, an increase in skills of 55%, the production of organic fertilizer products from agricultural waste.